Qici Sanling decoction suppresses bladder cancer growth by inhibiting the Wnt/Β-catenin pathway - Hua Gong; Weihua Chen; Lanhua Mi; Dan Wang; Youkang Zhao; Chao Yu; Aiguang Zhao (Taylor & Francis Group, 2019)
Context: Bladder cancer, which has high recurrence, is one of the most deadly cancers in the world. Astragalus propinquus Schischkin (Fabaceae) and Sagittaria sagittifolia L. (Alismataceae) are important herbs reported to be effective in cancer therapy. Objective: The efficacy of QCSL (Qici Sanling decoction) in bladder cancer treatment was examined. Materials and methods: T24 cells were injected into the flanks of nude mice and the mice were randomly divided into five groups: control; 20 mg/kg XAV-939 (an inhibitor of the WNT/β-catenin pathway); QCSL (100, 200, or 400 mg/kg). After 7 weeks, the mice were anaesthetised using isoflurane and the xenografts were excised to perform further experiments. Results: Both XAV-939 (tumour volume: 379.67 ± 159.92 mm3) and QCSL (796.18 ± 101.6 mm3) dramatically suppressed tumour growth comparing with control group (3612.12 ± 575.03 mm3). XAV-939 and QCSL treatments decreased cell proliferation from 56.3 ± 0.05% to 29.02 ± 0.07% and 37.51 ± 0.04%, respectively. In agreement, more infiltration of immune cells and pyknotic cells upon XAV-939 (apoptosis rates: 43.92 ± 0.03%) and QCSL (34.57 ± 0.04%) treatment comparing with control group (15.59 ± 0.03%) were observed. Furthermore, TUNEL staining of xenograft tumours illustrated more apoptotic cells upon XAV-939 and QCSL treatment. Mechanistically, XAV-939 and QCSL treatments significantly inhibited WNT/β-catenin pathway in T24 xenograft tumours. Discussion and conclusions: Our findings give new insights into the role of QCSL in bladder cancer and explore potential mechanisms contributing to the therapeutic effects of QCSL in bladder cancer.